QUALITY CONTROL OF REFINED SUGAR IN THE CARBONATATION PROCESS IN SUGAR COMPANIES - Julyanto , Octoberry; Apfiasari, Steela (AGUSPATI Research Institute, 2023)
Quality control in companies, both service companies and manufacturing companies, is very necessary. With the quality of the services or goods produced, the company hopes to attract consumers and fulfill consumer needs and desires. Quality control that is implemented well will have an impact on the quality of the products produced by the company. The quality of the products produced by a company is determined based on certain measurements and characteristics. Even though the production processes have been carried out well, in reality errors are still found where the quality of the product produced does not comply with standards or in other words the product produced is damaged or has defects in the product. Good product quality results from good quality control. So many companies use certain methods to produce a product with good quality. For this reason, quality control is needed to ensure that the products produced comply with applicable quality standards. The quality standards in question are raw materials, production processes and finished products ((Eric A. Hanushek & Wößmann, 2014)Therefore, quality control activities can be carried out starting from raw materials, during the production process until the final product and adjusted to the established standards. There are many methods that regulate or discuss quality with their respective characteristics. Broadly speaking, the meaning of food quality control is that it covers the environment from the company level to the national level which covers all aspects including policy, standardization, control, quality assurance, quality development, and legislation. This quality control covers all types of food products as well as all processing methods and production levels. Supervision of food quality cannot be separated from quality control. This quality control is intended for industrial companies whose production systems can be controlled. For example, control over the type, quantity and quality of products. This quality control also aims to prevent food fraud from circulating in the community. The existence of food adulteration stems from limited production land and an increase in market demand due to an increase in consumer purchasing power. This increase in market needs will lead to innovation and production of new products to address increasing consumer needs